(untitled) (Journal of Oriental Studies, 2023)
Sustainable development is a global issue aimed at solving environmental problems such as climate change caused by poor waste management. Although the problem affects all communities and countries, its effects differ depending on the management strategies. The study’s primary purpose was to investigate the impact of environmental awareness and education to solve waste problems. It is significant since it provides detailed information that might be used to develop environmental strategies to contain the menace. The authors approached the investigation using a systematic literature review, which involved gathering and synthesizing information about the research title and concluding based on insights gained. The results indicate that Japan has a long history of protecting the environment through various initiatives, such as law enactment and incorporating environmental education into the school curriculum. Although Japanese culture encourages individuals, organizations, and communities to respect the environment, the government should introduce robust measures, such as subsidizing recycling to encourage waste reduction. The findings are significant since the information is useful to integrate appropriate environmental programs in domestic schools to encourage innovation and ensure everyone makes waste management a personal responsibility.